2003
DOI: 10.1095/biolreprod.102.011494
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of Follicle-Stimulating Hormone Receptor Messenger RNA Expression in the Baboon Fetal Ovary1

Abstract: In the adult ovary, pituitary FSH via interaction with its receptor (FSHR) is required for follicular maturation and granulosa cell development. In humans and nonhuman primates, the pool of follicles available for adult ovarian function is established in utero. However, our understanding of the ontogeny and developmental regulation of FSHR in the ovary of the primate fetus is incomplete. Our goal was to determine whether the baboon fetal ovary expresses the full-length FSHR mRNA transcript and whether levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…Thus, fetal follicle-stimulating hormone levels were negatively correlated with ovarian folliculogenesis, declined between mid and late gestation, and remained elevated in estrogensuppressed animals in which follicle formation was markedly reduced [10]. The results of the current study show that in female but not male fetuses, fetal pituitary LH expression also declined between mid and late gestation and was prevented in estrogen-suppressed animals; these findings further support this hypothesis.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, fetal follicle-stimulating hormone levels were negatively correlated with ovarian folliculogenesis, declined between mid and late gestation, and remained elevated in estrogensuppressed animals in which follicle formation was markedly reduced [10]. The results of the current study show that in female but not male fetuses, fetal pituitary LH expression also declined between mid and late gestation and was prevented in estrogen-suppressed animals; these findings further support this hypothesis.…”
Section: Discussionsupporting
confidence: 82%
“…We showed previously that the estrogen-dependent ontogenesis in fetal ovarian follicle formation did not appear to reflect an action of fetal pituitary gonadotropins [10]. Thus, fetal follicle-stimulating hormone levels were negatively correlated with ovarian folliculogenesis, declined between mid and late gestation, and remained elevated in estrogensuppressed animals in which follicle formation was markedly reduced [10].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Serum LH and FSH levels were measured by RIA using antibodies/reagents and procedures established for the baboon, as described previously [10,32]. The baboon FSH and LH RIA had intra-assay coefficients of variation of 5.4% and 6.2%, respectively, interassay coefficients of variation of 6.9% and 4.5%, respectively, and a minimal detectable dose of 0.009 ng/tube [10,32].…”
Section: Radioimmunoassaysmentioning
confidence: 99%
“…Thus, in baboons in which estrogen was suppressed by treatment with the aromatase inhibitor letrozole during the second half of gestation, the number of primordial follicles formed in the fetal ovary was reduced by more than 50% [6], and the majority of follicles that developed contained unhealthy oocytes [7]. Additional studies showed that this critical action of estrogen most likely is elicited directly on the fetal ovary, which expresses estrogen receptor (ER) a/b [8,9], and not indirectly via fetal pituitary gonadotrophin support, fetal ovarian follicle-stimulating hormone (FSH) receptor expression [10], or fetal pituitary prolactin secretion [11]. Collectively, these observations, plus the fact that fetal ovarian folliculogenesis and oocyte integrity were normal in baboons treated with letrozole and estradiol, support our hypothesis that placental estrogen programs fetal ovarian development and regulates formation of the stockpile of healthy follicles critical for long-term survival [5,6] and presumably reproductive function in adulthood.…”
Section: Introductionmentioning
confidence: 99%